Green IT: an Awareness Survey Among Academicians and Administrative Staffs in Malaysian Public Universities. - Zairah Ab Rahim, Nor; Samuri, Norazila (International Journal of Engineering and Technology, 2018)
IT plays an important role in human life and industry in the whole world such as in manufacturing, transporting, medical, tourism and education. However, IT became one of the contributors to the Carbon Dioxide (CO2) emission that cause global warming. To reduce CO2 emissions by IT device, Green IT had been introduced. Green IT is an activity or action that being used and implemented to minimize the harmful of IT devices to the environment. The government of Malaysia had introduced Green IT in Malaysia since 2009. Despite of that, the awareness level of Green IT among Malaysian is still low and empirical study regarding Green IT awareness among academician is still unexplored. This paper study on the awareness regarding Green IT among academicians and administrative staffs in public universities. There were 245 academicians and administrative staffs were involved as respondents. Descriptive statistics had been used in this study. Overall, the finding shows that the level of Green IT awareness among academicians and administrative staffs was at moderate level. Finally, some issues had identified as barriers to the implementation of Green IT in the public universities such as lacking of support from staff, unrealized the existence of Green IT guideline, and lacking of enforcement. Some initiatives should be done to educate people and enhance their awareness about Green IT.Â